Glycolysis Define Two Prognostic Subgroups of Lung Adenocarcinoma With Different Mutation Characteristics and Immune Infiltration Signatures - Huo, Chen; Zhang, Meng-Yu; Li, Rui; Liu, Ting-Ting; Li, Jian-Ping; Qu, Yi-Qing (Frontiers in Cell and Developmental Biology, 2021)
Increasing evidences have proved that malignant tumors are associated with energy metabolism. This study was aimed to explore biological variables that impact the prognosis of patients in the glycolysis-related subgroups of lung adenocarcinoma (LUAD). The mRNA expression profiling and mutation data in large LUAD samples were collected from the Cancer Genome Atlas (TCGA) database. Then we identified the expression level and prognostic value of glycolysis-related genes, as well as the fractions of 22 immune cells in the tumor microenvironment. The difference between glycolysis activity, mutation and immune infiltrates were discussed in these groups, respectively. 255 glycolysis-related genes were identified from Gene set enrichment analysis (GSEA), of which 43 genes had prognostic values (p<0.05). Next, we constructed a glycolysis-related competing endogenous RNA (ceRNA) network which related to the survival of LUAD. Then two subgroups of LUAD (cluster 1 and 2) were identified by applying unsupervised consensus clustering to 43 glycolysis-related genes. The survival analysis showed that the cluster 1 patients had a worse prognosis (p<0.001), and up-regulated differentially expressed genes (DEGs) are interestingly enriched in malignancy-related biological processes. The difference between two subgroups is SPTA1, KEAP1, USH2A and KRAS among top 10 mutated signature, which may be the underlying mechanism of grouping. Combined high tumor mutational burden (TMB) with tumor subgroups preferably predict prognosis of LUAD patients. The CIBERSORT algorithm results revealed that low TMB samples were concerned with increased infiltration level of Memory resting CD4+ T cell (p=0.03), resting mast cells (p=0.044) and neutrophils (p=0.002) in cluster 1 and high TMB samples were concerned with increased infiltration level of memory B cells, Plasma cells, CD4 memory activated T cells, Macrophages M1 and activated Mast cells in cluster 2. While reduced infiltration of Monocytes, resting dendritic cells and resting mast cells were captured in cluster 2. In Conclusion, significant different gene expression characteristic were pooled according to the two subgroups of LUAD. The combination of subgroups, TMB and tumor-infiltrating immune cell signature might be novel prognostic biomarkers in LUAD.